The difference that is me. - Soh, Audrie Pei Yi. (2010)
This essay will examine, in three parts, the colonizers' reliance on binary oppositions and Said's Orientalism in their relationship with their colonies, as well as the impact of this reliance, on Jean Rhys' 'WIde Sargasso Sea' and Charlotte Bronte's 'Jane Eyre'.